-
Notifications
You must be signed in to change notification settings - Fork 2
/
Copy path12.tex
441 lines (397 loc) · 14.6 KB
/
12.tex
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
408
409
410
411
412
413
414
415
416
417
418
419
420
421
422
423
424
425
426
427
428
429
430
431
432
433
434
435
436
437
438
439
440
441
\section{Lecture -- Week 12}
%\subsection{The inverse Galois problem}
\subsection{Group cohomology}
Let $G$ be a group and $A$ be a \emph{(left) $G$-module}. This means that $A$ is an abelian
group together with a map
\[
G\times A\to A,\quad
(g,a)\mapsto g\cdot a
\]
such that $1\cdot a=a$ for all $a\in A$, $(gh)\cdot a=g\cdot (h\cdot a)$ for
all $g,h\in G$ and $a\in A$ and $g\cdot (a+b)=g\cdot a+g\cdot b$ for
all $g\in G$ and $a,b\in A$.
\begin{example}
The group $\Gal(\C/\R)$ acts on $\C$ and $\C^\times$. Moreover,
it acts trivially on $\R$ and $\R^\times$.
\end{example}
More generally, if $E/K$ is a finite Galois extension, then
the Galois group $\Gal(E/K)$ acts on $E$ and $E^\times$.
\begin{definition}
Let $G$ be a group and $M$ and $N$ be $G$-modules. A map
$f\colon M\to N$ is a \emph{homomorphism} of $G$-modules
if $f(\sigma\cdot m)=\sigma\cdot f(m)$ for all $m\in M$ and $\sigma\in G$.
\end{definition}
\begin{definition}
Let $G$ be a group and $M$ be a $G$-module.
The submodule of \emph{$G$-invariants} is defined as
\[
M^G=\{m\in M:\sigma\cdot m=m\text{ for all $\sigma\in G$}\}.
\]
\end{definition}
Note that $M^G$ is the largest submodule of the $G$-module
$M$ where $G$ acts trivially. For example, if
$G=\Gal(E/K)$, then $E^G=K$.
\begin{proposition}
\label{pro:H0}
Let $G$ be a group. If the sequence
of $G$-modules and $G$-module homomorphism
\[
\begin{tikzcd}
0 & P & M & N & 0
\arrow[from=1-1, to=1-2]
\arrow["\alpha", from=1-2, to=1-3]
\arrow["\beta", from=1-3, to=1-4]
\arrow[from=1-4, to=1-5]
\end{tikzcd}\]
is exact, then
\[
\begin{tikzcd}
0 & P^G & M^G & N^G
\arrow[from=1-1, to=1-2]
\arrow["\alpha^0", from=1-2, to=1-3]
\arrow["\beta^0", from=1-3, to=1-4]
\end{tikzcd}
\]
is exact, where $\alpha^0$ is the restriction $\alpha|_{P^G}$ of $\alpha$ to $P^G$ and
$\beta^0$ is the restriction $\beta|_{M^G}$ of $\beta$ to $M^G$.
\end{proposition}
\begin{proof}
Since $\alpha$ is injective, the restriction $\alpha^0$ is injective.
Note that
$\ker\beta^0=\ker\beta\cap M^G\subseteq\ker\beta$.
We claim
that $\alpha^0(P^G)=\alpha(P)\cap M^G$. If $m\in\alpha(P)\cap M^G$, then
$\alpha(p)=m$ for some $p\in P$ and $\sigma\cdot m=m$. Since
\[
\alpha(p)=m=\sigma\cdot m=\sigma\cdot\alpha(p)=\alpha(\sigma\cdot p),
\]
$\sigma\cdot p-p\in\ker\alpha=\{0\}$. Hence $\sigma\cdot p=p$ and
$p\in P^G$. Conversely, if $m\in\alpha^0(P^G)$, then
$m=\alpha(p)$ for some $p\in P^G$. If $\sigma\in G$, then
\[
\sigma\cdot m=\sigma\cdot\alpha(p)=\alpha(\sigma\cdot p)=\alpha(p)=m.
\]
Hence $m\in M^G\cap\alpha(P)$.
Now
\[
\alpha^0(P^G)=\alpha(P)\cap M^G=\ker\beta\cap M^G=\ker\beta^0.\qedhere
\]
\end{proof}
Note that in the previous proposition, we did not prove that
the map $\beta|_{M^G}$ is surjective.
\begin{example}
Let $G=\Gal(\C/\R)$. Consider the following exact sequence
of $G$-modules:
\[
\begin{tikzcd}
1 & \{-1,1\} & \C^\times & \C^\times & 1
\arrow[from=1-1, to=1-2]
\arrow[from=1-2, to=1-3]
\arrow["\beta", from=1-3, to=1-4]
\arrow[from=1-4, to=1-5]
\end{tikzcd}
\]
where $\beta(z)=z^2$. Note that $\beta$ is surjective. Take invariants
to obtain the sequence
\[
\begin{tikzcd}
0 & \{-1,1\} & \R^\times & \R^\times
\arrow[from=1-1, to=1-2]
\arrow[from=1-2, to=1-3]
\arrow["\beta^0", from=1-3, to=1-4]
\end{tikzcd}
\]
where $\beta^0(x)=x^2$. Note that $\beta^0$ is not surjective!
\end{example}
\begin{definition}
Let $G$ be a group and $N$ be a $G$-module.
We define
\begin{align*}
H^0(G,M)&=M^G,\\
C^1(G,M)&=\{\phi\colon G\to M:\phi\text{ is a map}\},\\
Z^1(G,M)&=\{\phi\in C^1(G,M):\phi(\sigma\tau)=\phi(\sigma)+\sigma\cdot\phi(\tau)\text{ for all $\sigma,\tau\in G$}\},
\end{align*}
\end{definition}
Note that $Z^1(G,M)$ is an abelian group with the operation
\[
(\phi+\phi_1)(\sigma)=\phi(\sigma)+\phi_1(\sigma).
\]
Moreover, if $\phi\in Z^1(G,M)$, then
$\phi(1_G)=0_M$. To prove this fact, note that
\[
\phi(1_G)=\phi(1_G1_G)=\phi(1_G)+1_G\cdot\phi(1_G)=\phi(1_G)+\phi(1_G)
\]
implies
that $\phi(1_G)=0_M$.
\begin{example}
\label{exa:BinZ}
Let $G$ be a group and $M$ be a $G$-module. Fix $m\in M$. Then
the map $\phi\colon G\to M$, $\phi(\sigma)=\sigma\cdot m-m$, is an element
of $Z^1(G,M)$, because
\begin{align*}
\phi(\sigma\tau)&=(\sigma\tau)\cdot m-m\\
&=(\sigma\tau)\cdot m-\sigma\cdot m+\sigma\cdot m-m\\
&=\sigma\cdot (\tau\cdot m-m)+\sigma\cdot m-m\\
&=\sigma\cdot \phi(\tau)+\phi(\sigma)
\end{align*}
for all $\sigma,\tau\in G$.
\end{example}
\begin{definition}
Let $G$ be a group and $M$ be a $G$-module. The set
$B^1(G,M)$ of \emph{coboundaries} is the set
of elements $\phi\in C^1(G,M)$ such that there is a fixed
$m\in M$ such that
$\phi(\sigma)=\sigma\cdot m=m$ for all $\sigma\in G$.
\end{definition}
We proved in Example \ref{exa:BinZ} that
$B^1(G,M)\subseteq Z^1(G,M)$. A direct calculation shows that, in fact,
$B^1(G,M)$ is a subgroup of $Z^1(G,M)$.
\begin{definition}
Let $G$ be a group and $M$ be a $G$-module. The
\emph{first cohomology group} of $G$ with coefficients
in $M$ is defined as the quotient
\[
H^1(G,M)=Z^1(G,M)/B^1(G,M).
\]
\end{definition}
\begin{example}
If $G$ acts trivially on $M$, then
\[
H^0(G,M)=M^G=M,
\quad
B^1(G,M)=\{0\},
\quad
Z^1(G,M)=\Hom(G,M).
\]
Hence
$H^1(G,M)\simeq\Hom(G,M)$.
\end{example}
\begin{example}
Let $G=\Gal(\C/\R)=\{\id,\gamma\}$, where $\gamma\colon\C\to\C$, $z\mapsto\overline{z}$, is the complex conjugation. Then
\[
H^0(G,\R^\times)=\left(\R^\times\right)^G=\R^\times.
\]
Since $G$ acts trivially on $\R^\times$,
\[
H^1(G,\R^\times)=\Hom(G,\R^\times)\simeq\Hom(G,\{-1,1\})\simeq\Z/2.
\]
\end{example}
The following lemma will be useful.
\begin{lemma}
\label{lem:H1_maps}
Let $G$ be a group and
$\alpha\colon M\to N$ be a homomorphism of $G$-modules.
Then
\[
\alpha^1\colon H^1(G,M)\to H^1(G,N),\quad
\phi+B^1(G,M)\mapsto \alpha\circ\phi+B^1(G,N),
\]
is a group homomorphism.
\end{lemma}
\begin{proof}
Let us prove that the map $\alpha^1$ is well-defined. If
$\phi-\phi'\in B^1(G,M)$, then
there exists a fixed
$m\in M$ such that
$(\phi-\phi')(\sigma)=\sigma\cdot m-m$ for all $\sigma\in G$.
Let $n=\alpha(m)\in N$.
For $\sigma\in G$,
\[
\alpha((\phi-\phi')(\sigma))=\alpha(\sigma\cdot m-m)
=\sigma\cdot \alpha(m)-\alpha(m)=\sigma\cdot n-n.
\]
Thus $\alpha\circ\phi-\alpha\circ\phi'\in B^1(G,N)$.
We now prove that $\alpha^1$ is a group homomorphism. If
$\phi,\phi'\in Z^1(G,M)$, then
\begin{align*}
\alpha^1(\phi+B^1(G,M)+\phi'+B^1(G,M))
&=\alpha^1(\phi+\phi'+B^1(G,M))\\
&=\alpha\circ(\phi+\phi')+B^1(G,N)\\
&=\alpha\circ\phi+\alpha\circ\phi'+B^1(G,N)\\
&=\alpha\circ\phi+B^1(G,N)+\alpha\circ\phi'+B^1(G,N)\\
&=\alpha^1(\phi+B^1(G,M))+\alpha^1(\phi'+B^1(G,M)).\qedhere
\end{align*}
\end{proof}
We will provide a detailed proof of the upcoming result.
The theorem will be established by applying a \emph{diagram chasing} technique, a widely used tool in homological algebra.
The proof is tedious and may seem intricate, but the method essentially
involves ``chasing'' elements around a (commutative) diagram until we attain the desired result.
\begin{theorem}
Let $G$ be a group and
\[
\begin{tikzcd}
0 & P & M & N & 0
\arrow[from=1-1, to=1-2]
\arrow["\alpha", from=1-2, to=1-3]
\arrow["\beta", from=1-3, to=1-4]
\arrow[from=1-4, to=1-5]
\end{tikzcd}
\]
be an exact sequence of $G$-modules and $G$-module homomorphism.
Then there exists a \emph{connection homomorphism} $\delta$ such that the sequence
\begin{equation}
\label{eq:long}
\begin{tikzcd}
0\rar & H^0(G,P)\rar["\alpha^0"] & H^0(G,M) \rar["\beta^0"]
\ar[draw=none]{d}[name=X, anchor=center]{}
& H^0(G,N) \ar[rounded corners,
to path={ -- ([xshift=2ex]\tikztostart.east)
|- (X.center) \tikztonodes
-| ([xshift=-2ex]\tikztotarget.west)
-- (\tikztotarget)}]{dll}[at end]{\delta} \\
&H^1(G,P) \rar["\alpha^1"] & H^1(G,M) \rar["\beta^1"] & H^1(G,N)
\end{tikzcd}
\end{equation}
of abelian groups
and group homomorphisms is exact.
\end{theorem}
\begin{proof}
By Proposition \ref{pro:H0}, the long
sequence~\eqref{eq:long} is exact at $H^0(G,P)=P^G$,
$H^0(G,M)=M^G$ and
$H^0(G,N)=N^G$. Note that, in particular,
$\alpha\colon P\to\alpha(P)$ is a bijective group homomorphism.
Let us construct the connecting
homomorphism $\delta\colon H^0(G,N)\to H^1(G,P)$. For
$n\in N^G$, let $m\in M$ be such that
$\beta(m)=n$. We define $\delta(n)=\phi+B^1(G,P)$, where
\[
\phi(\sigma)=\alpha^{-1}(\sigma\cdot m-m).
\]
Note that $\sigma\cdot m-m\in\im\alpha=\ker\beta$, as
\[
\beta(\sigma\cdot m-m)=\sigma\cdot \beta(m)-\beta(m)=\sigma\cdot n-n=0.
\]
Let us prove that the map $\delta$ is well-defined: if $m,m'\in M$ are such that
\[
\beta(m)=\beta(m')=n,
\]
then $m-m'\in\ker\beta=\alpha(P)$.
For $\sigma\in G$, write $\phi'(\sigma)=\sigma\cdot m'-m'$.
Since
$m-m'=\alpha(p)$ for some $p\in P$ and
$\alpha^{-1}$ is a homomorphism of $G$-modules,
\begin{align*}
\phi(\sigma)-\phi'(\sigma)&=\alpha^{-1}(\sigma\cdot m-m)
-\alpha^{-1}(\sigma\cdot m'-m')\\
&=\alpha^{-1}(\sigma\cdot (m-m'))-\alpha^{-1}(m-m')\\
&=\alpha^{-1}(\sigma\cdot\alpha(p)-\alpha(p))\\
&=\sigma\cdot p-p.
\end{align*}
Thus $\phi-\phi'\in B^1(G,P)$.
Note that $\phi\in Z^1(G,P)$, because
\begin{align*}
\phi(\sigma\tau)&=\alpha^{-1}((\sigma\tau)\cdot m-m)\\
&=\alpha^{-1}((\sigma\tau)\cdot m-\sigma\cdot m+\sigma\cdot m-m)\\
&=\alpha^{-1}(\sigma\cdot (\tau\cdot m-m))+\alpha^{-1}(\sigma\cdot m-m)\\
&=\sigma\cdot\phi(\tau)+\phi(\sigma)
\end{align*}
holds for all $\sigma,\tau\in G$.
We now prove that the sequence \eqref{eq:long}
is exact at $H^0(G,N)=N^G$. We need to prove that $\ker\delta=\im\beta^0$. To prove $\supseteq$ note that if $m\in M^G$ is such that
$\delta(\beta(m))=\phi+B^1(G,P)$, then
\[
\phi(\sigma)=\alpha^{-1}(\sigma\cdot m-m)=0.
\]
Conversely, if $n\in\ker\delta$, then there exists $m\in M$ such that $\beta(m)=n$ and
\[
\delta(\beta(m))=\phi+B^1(G,P),
\]
where $\phi\in B^1(G,P)$ and
$\phi(\sigma)=\alpha^{-1}(\sigma\cdot m-m)$
for all $\sigma\in G$. Since $\phi\in B^1(G,P)$, there
exists $p\in P$ such that $\phi(\sigma)=\sigma\cdot p-p$ for all $\sigma\in G$. Note that
\[
\beta(m-\alpha(p))=\beta(m)-\beta(\alpha(p))=\beta(m)=n.
\]
Moreover, $m-\alpha(p)\in M^G$, as $\sigma\cdot (m-\alpha(p))=m-\alpha(p)$. Hence $n\in\im\beta^0$.
We now prove that \eqref{eq:long} is exact at $H^1(G,P)$, that
is $\im\delta=\ker\alpha^1$. To prove
$\subseteq$ note that
for $n\in N^G$, $\delta(n)=\phi+B^1(G,P)$, where
$\phi(\sigma)=\alpha^{-1}(\sigma\cdot m-m)$ for all $\sigma\in G$
and some $m\in M$ such that $\beta(m)=n$. In particular,
$\alpha\circ\phi\in B^1(G,M)$.
Then
\[
\alpha^1(\phi+B^1(G,P))=\alpha\circ\phi+B^1(G,M)=B^1(G,M).
\]
To prove $\supseteq$, let $\phi+B^1(G,P)\in\ker\alpha^1$. Then
$\alpha\circ\phi\in B^1(G,M)$, that is $\alpha(\phi(\sigma))=\sigma\cdot m-m$ for
all $\sigma\in G$ and some $m\in M$. Note that
\[
\delta(\beta(m))=\psi+B^1(G,P),
\]
where $\psi(\sigma)=\alpha^{-1}(\sigma\cdot m-m)$. This implies that
$\alpha(\psi(\sigma))=\alpha(\phi(\sigma))$ for all $\sigma\in G$. Since
$\alpha$ is injective, $\psi=\phi$. Therefore
$\phi+B^1(G,P)$ belongs to the image of $\delta$.
Finally, we prove that the sequence \eqref{eq:long} is exact
at $H^1(G,M)$, that is $\im\alpha^1=\ker\beta^1$. To prove $\subseteq$
note that
\[
\beta^1(\alpha^1(\phi+B^1(G,P)))=\beta^1(\alpha\circ\phi+B^1(G,M))
=(\beta\circ\alpha)\circ\phi+B^1(G,N)=B^1(G,N).
\]
Conversely, let $\phi+B^1(G,M)\in\ker\beta_1$. Then $\beta\circ\phi\in B^1(G,N)$. Thus
there exists $n\in N$ such that $\beta(\phi(\sigma))=\sigma\cdot n-n$
for all $\sigma\in G$. Since $\beta$ is surjective,
$n=\beta(m)$ for some $m\in M$. Hence
\[
\beta(\phi(\sigma))=\sigma\cdot n-n=\sigma\cdot \beta(m)-\beta(m)
=\beta(\sigma\cdot m-m).
\]
For each $\sigma\in G$,
$\phi(\sigma)-(\sigma\cdot m-m)\in\ker\beta=\im\alpha$.
and therefore $\phi(\sigma)-(\sigma\cdot m-m)=\alpha(\rho_\sigma)$.
This defines a map $\rho\colon G\to P$, $\sigma\mapsto\rho_\sigma$.
We claim that $\rho\in Z^1(G,P)$. If $\sigma,\tau\in G$, then
\begin{align*}
\alpha(\rho_{\sigma\tau})&=\phi(\sigma\tau)-( (\sigma\tau)\cdot m-m)\\
&=\phi(\sigma)+\sigma\cdot\phi(\tau)-(\sigma\cdot (\tau\cdot m-m)+\sigma\cdot m-m)\\
&=\alpha(\rho_\sigma)+\sigma\cdot\alpha(\rho_\tau).
\end{align*}
Since $\alpha$ is injective, it follows that $\rho\in Z^1(G,P)$.
Now
\[
\alpha_1(\rho+B^1(G,P))=\alpha\circ\rho+B^1(G,M)=\phi+B^1(G,M).\qedhere
\]
\end{proof}
\begin{theorem}
Let $G$ be a finite group and $M$ be a $G$-module.
Then
\[
|G|H^1(G,M)=\{0\}.
\]
\end{theorem}
\begin{proof}
Let $n=|G|$. It is enough to prove that
if $\phi\in Z^1(G,M)$, then $n\phi\in B^1(G,M)$. Let $\phi\in Z^1(G,M)$ and
$\sigma\in G$. Then
\[
\phi(\sigma\tau)=\phi(\sigma)+\sigma\cdot\phi(\tau)
\]
for all $\tau\in G$. Summing over all possible $\tau\in G$, we obtain that
\begin{equation}
\label{eq:|G|H1(G,M)=0}
\sum_{\tau\in G}\phi(\tau)=\sum_{\tau\in G}\phi(\sigma\tau)
=\sum_{\tau\in G}\sigma\cdot\phi(\tau)+\sum_{\tau\in G}\phi(\sigma)=n\phi(\sigma).
\end{equation}
Let $m=-\sum_{\tau\in G}\phi(\tau)\in M$. Then
\eqref{eq:|G|H1(G,M)=0} can be rewritten as
\[
-m=\sum_{\tau\in G}\phi(\tau)=\sigma\cdot \sum_{\tau\in G}\phi(\tau)+n\phi(\sigma)
=-\sigma\cdot m+n\phi(\sigma).
\]
Thus $n\phi(\sigma)=\sigma\cdot m-m$ and hence $n\phi\in B^1(G,M)$.
\end{proof}
\begin{exercise}
Let $G$ be a finite group and
$M$ be a finite $G$-module of size coprime to $|G|$. Prove that
$H^1(G,M)=\{0\}$.
\end{exercise}
\begin{exercise}
Let $G$ be a finite group and
$M$ be a finitely generated $G$-module. Prove that
$H^1(G,M)$ is finite.
\end{exercise}